Anti-apoptotic properties of carbon monoxide in porcine oocyte during in vitro aging - Němeček, David; Dvořáková, Markéta; Heroutová, Ivona; Chmelíková, Eva; Sedmíková, Markéta (PeerJ, 2017)
If fertilization of matured oocyte does not occur, unfertilized oocyte undergoes aging, resulting in a time-dependent reduction of the oocyte's quality. The aging of porcine oocytes can lead to apoptosis. Carbon monoxide (CO), a signal molecule produced by the heme oxygenase (HO), possesses cytoprotective and anti-apoptotic effects that have been described in somatic cells. However, the effects of CO in oocytes have yet to be investigated. By immunocytochemistry method we detected that both isoforms of heme oxygenase (HO-1 and HO-2) are present in the porcine oocytes. Based on the morphological signs of oocyte aging, it was found that the inhibition of both HO isoforms by Zn-protoporphyrin IX (Zn-PP IX) leads to an increase in the number of apoptotic oocytes and decrease in the number of intact oocytes during aging. Contrarily, the presence of CO donors (CORM-2 or CORM-A1) significantly decrease the number of apoptotic oocytes while increasing the number of intact oocytes. We also determined that CO donors significantly decrease the caspase-3 (CAS-3) activity. Our results suggest that HO/CO contributes to the sustaining viability through regulation of apoptosis during in vitro aging of porcine oocytes.
Keywords: Pigs; Antiapoptotic; Aging; Heme oxygenase; Carbon monoxide; Oocyte; Caspase-3